EFFECT OF SUBLETHAL CONCENTRATION OF MALATHION ON HEMATOLOGICAL PARAMETERS OF MONOPTERUS CUCHIA (HAMILTON- BUCHANAN) - BARUAH, INDIRA; U. C. GOSWAMI; BORAH, BIBHA CHETIA; BHUYAN, SONMOINA (The Bioscan, 2013)
Impact of pesticides used in agricultural operations on the environment as well biotic community as a whole is a global concern particularly in developing countries like India. The present study encompasses impact of sub lethal concentration of a commonly used OP pesticide ‘Malathion’ on certain hematological parameters of Monopterus cuchia (Ham- Buch) popularly known as ‘mud eel’ under laboratory condition. The study revealed significant decrease in Total Erythrocyte Count (TEC) in treated fish upon exposure to sub lethal dose of Malathion with a mean value of (2.02 ± 0.2) 106/mm3 in comparison to the control (2.49 ± 0.2) 106/mm3. In addition to that, significant increase in leucocytes count in treated fish with a mean value of 2.57 ± 0.5 106/mm3 in comparison to control (2.00 ± 0.5) 106/mm3 indicated ailing condition of the fish. Significant difference in percentage of Eosinophil, Neutrophils, Lymphocytes, Monocytes in blood samples of controlled and treated fish indicates the enormity of the impact of the pesticide on the hematological parameters of the fish. Although immediate mortality was not recorded, the findings indicated that prolonged exposure may have severe impact on the life processes of the species.